2018
DOI: 10.1042/bsr20181787
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the ligand binding site of placental protein 13/galectin-13 recovers its ability to bind lactose

Abstract: Placental protein 13/galectin-13 (Gal-13) is highly expressed in placenta, where its lower expression is related to pre-eclampsia. Recently, the crystal structures of wild-type Gal-13 and its variant R53H at high resolution were solved. The crystallographic and biochemical results showed that Gal-13 and R53H could not bind lactose. Here, we used site-directed mutagenesis to re-engineer the ligand binding site of wild-type Gal-13, so that it could bind lactose. Of six newly engineered mutants, we were able to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…At position 55 in Gal‐13 and Gal‐14, there is an arginine residue, whereas in Gal‐1, Gal‐3, and Gal‐8, there is an asparagine at the same position. Previously, we mutated Arg55 in Gal‐13 to an asparagine and found that this mutation did not influence lactose binding [17]. This indicates that the residues at this position might regulate the ligand‐binding specificity of galectins.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…At position 55 in Gal‐13 and Gal‐14, there is an arginine residue, whereas in Gal‐1, Gal‐3, and Gal‐8, there is an asparagine at the same position. Previously, we mutated Arg55 in Gal‐13 to an asparagine and found that this mutation did not influence lactose binding [17]. This indicates that the residues at this position might regulate the ligand‐binding specificity of galectins.…”
Section: Resultsmentioning
confidence: 95%
“…In Gal‐13, there is also a histidine residue (His57) in the lactose‐binding site. However, previous Gal‐13 studies showed that only the variant having an arginine at this position could bind lactose [17]. In fact, when both Arg53 and His57 in Gal‐13 were mutated to His53 and Arg57, Gal‐13 regained its ability to bind lactose.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 3C shows that these could be due to the fact it lacks 4 out of the 6 most conserved residues, the previously described His, Asn, Arg, and Trp of subsite C. A second special case is Gal-13 (also known as Placenta Protein 13), which has proven to be unable to bind lactose by both crystallographic and biochemical analysis. However, the Gal-13 R53H-H57R double mutant (PDB id: 6a62) was proven to recover the lactose-binding capabilities (Su et al, 2018a), thus suggesting that it possibly changed its binding capacity due to a few recent evolutionary steps. The structural explanation behind this clever work of re-engineering lays in the fact that in Gal-13 position 53 corresponds to the key His and position 57 to the Arg of subsite C, which as mentioned above are necessary for hydrogen bonding the axial C4-OH.…”
Section: Galectin Carbohydrate Recognitionmentioning
confidence: 99%